The circular economy mirage: a lifecycle systems analysis of India’s vehicle scrappage policy - Aladdin H. M. Shaker; Puneet Pathak (Environment Systems and Decisions, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

Water Use in Rice Crop Cultivation in India: A Quantitative Assessment - Manish Debnath; Sumanta Chatterjee; A. K. Nayak; D. Chakraborty; H. Pathak (Agricultural Research, 2026)

Estimating carbon sequestration in orchards of semi-arid tropics: A modeling approach - R Siddesh; H. Pathak; S.B. Chavan; V.D. Kakade; S.S. Salunkhe; A.R. Uthappa; N. Paul; H.M. Halli; K.S. Reddy (Biomass and Bioenergy, 2026)

Targeting west nile virus replication by xanthine inhibitors - Theresa H. Nguyen; Jessica L. Smith; Shuklendu D. Karyakarte; John P. Tillotson; Sarath C. Sarngadharan; Fuad Al Abir; Jake Y. Chen; Sixue Zhang; Lynn Rasmussen; Robert Bostwick; Alec J. Hirsch; Corinne E. Augelli-Szafran; et al. (Medicinal Chemistry Research, 2025)

Recent advancement on nanotechnology and natural compounds for skin UV protection: a review - M. J. Saadh; V. Jain; M. M. Rekha; P. K. Pathak; H. M. Ahmed; K. Satyam Naidu; B. Juneja; F. Faez Sead; M. Dehghanipour (International Journal of Environmental Science and Technology, 2025)

Modified emission and scaling factors for methane and nitrous oxide in rice system of India: A country specific disaggregate approach - Pratap Bhattacharyya; A. Bhatia; N. Jain; D. Chatterjee; S. Mohanty; M. Prabhakar; Pratibha M; N.N. Jambhulkar; S. Ananthakrishnan; S.K. Nayak; A.K. Nayak; H. Pathak (Journal of Environmental Management, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Inhibition of chondroitin sulphate-degrading enzyme Chondroitinase ABC by dextran sulphate - Sagar Dalal; Rachana Pathak; Edward X. S. Moh; Nicolle H. Packer (Glycoconjugate Journal, 2025)
Chondroitin sulphate (CS) is a sulphated glycosaminoglycan (GAG) polysaccharide found on proteoglycans (CSPGs) in extracellular and pericellular matrices. Chondroitinase ABC (CSase ABC) derived from Proteus vulgaris is an enzyme that has gained attention for the capacity to cleave chondroitin sulphate (CS) glycosaminoglycans (GAG) from various proteoglycans such as Aggrecan, Neurocan, Decorin etc. The substrate specificity of CSase ABC is well-known for targeting various structural motifs of CS chains and has gained popularity in the field of neuro-regeneration by selective degradation of CS GAG chains. Within this context, our investigation into the biochemistry of CSase ABC led us to a previously unreported inhibition of CSase ABC activity by Dextran Sulphate (DexS). To understand the inhibitory effects of DexS, we compared its inhibition of CSase ABC to that of other polysaccharides such as Heparan Sulphate, Heparin, Colominic Acid, Fucoidan, and Dextran. This analysis identified key structural factors such as monosaccharide composition and linkage, sulphation degree and overall charge as influencing CSase ABC inhibition. Remarkably, DexS emerged as a unique inhibitor of CSase ABC, with distinctive inhibitory effects that correlate with its chain length. DexS has been used to reliably induce ulcerative colitis in mice, effectively mimicking inflammatory bowel diseases in humans, and has been previously shown to inhibit both RNA polymerase and reverse transcriptase. Our investigation emphasizes the interplay between the properties of DexS and CSase ABC, providing significant insights into the utilization of polysaccharide-based inhibitors for modulating enzyme activity.

Prevalence and risk factor for H9N2 avian influenza virus in poultry retail shops of Madhya Pradesh - Baleshwari Dixit; H. V. Murugkar; S. Nagarajan; C. Tosh; Manoj Kumar; Anubha Pathak; Sivasankar Panickan; Neeraj Shrivastav; Anjani K. Mishra; Manu Dixit (VirusDisease, 2024)

Integration of apocarotenoid and transcriptome profiles of developing stigmas of saffron (Crocus sativus L.) reveals a multifaceted control involving PSY2, OR-a, PIF1 and HY5 genes in regulation of apocarotenoid biosynthesis - Mona H. Thakuri; Upasna Chettry; Jyoti Pathak; Nikhil K. Chrungoo (South African Journal of Botany, 2024)

Thyroid hormone dynamics of Tharparkar and Sahiwal cattle during induced heat stress - Anjali; Gururaj VK; Lipika Sarma; M. Tripathi; Med Ram Verma; Vinay Verma; M. C. Pathak; H. A. Samad; V. P. Maurya; V. S. Chouhan; Gyanendra Singh (Tropical Animal Health and Production, 2023)

Impact, adaptation, and mitigation of climate change in Indian agriculture - H. Pathak (Environmental Monitoring and Assessment, 2023)

Functionality of fructosphere bacteria Kocuria sediminis strain AC3 in plant growth promotion and biodegradation of the acephate in grape berries - Yogita H. Ranade; Sujoy Saha; Madhura Chandrashekar; Indu Sanjay Sawant; Raviraj C. Shinde; Pranav D. Pathak (Biologia, 2022)

Nutrient Budget in Indian Agriculture During 1970–2018: Assessing Inputs and Outputs of Nitrogen, Phosphorus, and Potassium - H. Pathak; Ram K. Fagodiya (Journal of Soil Science and Plant Nutrition, 2022)

Mechanistic insight of cell anti-proliferative activity of fluoroquinolone drug-based Cu(II) complexes - Divyang H. Gandhi; Foram U. Vaidya; Chandramani Pathak; Tushar N. Patel; Bhupesh S. Bhatt (Molecular Diversity, 2022)

Fungitoxicity profile of Cladosporium cladosporioides C1, as a leveraging tool for postharvest management of grapes - Yogita H. Ranade; Pranav D. Pathak; Madhura Chandrashekar; Sujoy Saha (Biologia, 2022)

Innovative trend analysis of spatio-temporal variations of rainfall in India during 1901–2019 - RN Singh; Sonam Sah; Bappa Das; Sunil Potekar; Amresh Chaudhary; H. Pathak (Theoretical and Applied Climatology, 2021)

Effect of Long-Term Organic Fertilization in Flooded Rice Soil on Phosphorus Transformation and Phosphate Solubilizing Microorganisms - Dibyendu Chatterjee; A. K. Nayak; Annapurna Mishra; C. K. Swain; U. Kumar; D. Bhaduri; P. Panneerselvam; B. Lal; P. Gautam; H. Pathak (Journal of Soil Science and Plant Nutrition, 2021)

Fluorescence, DNA Interaction and Cytotoxicity Studies of 4,5-Dihydro-1H-Pyrazol-1-Yl Moiety Based Os(IV) Compounds: Synthesis, Characterization and Biological Evaluation - Bharat H. Pursuwani; Bhupesh S. Bhatt; Foram U. Vaidya; Chandramani Pathak; Mohan N. Patel (Journal of Fluorescence, 2021)

Spatio-temporal trends and variability of rainfall in Maharashtra, India: Analysis of 118 years - RN Singh; Sonam Sah; Bappa Das; Lata Vishnoi; H. Pathak (Theoretical and Applied Climatology, 2021)

Water vapor flux in tropical lowland rice - Dibyendu Chatterjee; Amaresh Kumar Nayak; S. Vijayakumar; Manish Debnath; Sumanta Chatterjee; Chinmaya Kumar Swain; Priyanka Bihari; S. Mohanty; Rahul Tripathi; Mohammad Shahid; Anjani Kumar; H. Pathak (Environmental Monitoring and Assessment, 2019)

Generation of a selectable marker free, highly expressed single copy locus as landing pad for transgene stacking in sugarcane - Yang Zhao; Jae Y. Kim; Ratna Karan; Je H. Jung; Bhuvan Pathak; Bruce Williamson; Baskaran Kannan; Duoduo Wang; Chunyang Fan; Wenjin Yu; Shujie Dong; Vibha Srivastava; et al. (Plant Molecular Biology, 2019)

Interplay of phosphorus doses, cyanobacterial inoculation, and elevated carbon dioxide on yield and phosphorus dynamics in cowpea - Sumit Kumar Dey; B. Chakrabarti; T. J. Purakayastha; Radha Prasanna; R. Mittal; S. D. Singh; H. Pathak (Environmental Monitoring and Assessment, 2019)

Ecosystem services in different agro-climatic zones in eastern India: impact of land use and land cover change - Rahul Tripathi; K. C. Moharana; A. D. Nayak; B. Dhal; Md Shahid; B. Mondal; S. D. Mohapatra; P. Bhattacharyya; Nuala Fitton; Pete Smith; A. K. Shukla; H. Pathak; et al. (Environmental Monitoring and Assessment, 2019)

Synthesis, characterization and photocatalytic degradation of chlorpyrifos by novel Fe: ZnO nanocomposite material - Samreen Heena Khan; Bhawana Pathak; M. H. Fulekar (Nanotechnology for Environmental Engineering, 2018)

Application of BICOVOX catalyst for hydrogen production from ethanol - S. Sharma; B. Patil; A. Pathak; S. Ghosalkar; H. K. Mohanta; B. Roy (Clean Technologies and Environmental Policy, 2018)

Soil microbial responses as influenced by Jatropha plantation under rainfed condition in north-west India - Ahmad Mahmoud; S. D. Singh; K. S. Muralikrishna; H. Pathak; Namita Das Saha (Agroforestry Systems, 2018)

Simulation of leaf blast infection in tropical rice agro-ecology under climate change scenario - K. Viswanath; P. Sinha; S. Naresh Kumar; Taru Sharma; Shalini Saxena; Shweta Panjwani; H. Pathak; Shalu Mishra Shukla (Climatic Change, 2017)

Weed and Nitrogen Management Effects on Weed Infestation and Crop Productivity of Wheat–Mungbean Sequence in Conventional and Conservation Tillage Practices - C. P. Nath; T. K. Das; K. S. Rana; R. Bhattacharyya; H. Pathak; S. Paul; M. C. Meena; S. B. Singh (Agricultural Research, 2017)

Super-Optimal NPK Along with Foliar Iron Application Influences Bioavailability of Iron and Zinc of Wheat - Rajiv Rakshit; A. K. Patra; T. J. Purakayastha; R. D. Singh; H. Pathak; Shiva Dhar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Juvenile myelomonocytic leukemia due to a germline CBL Y371C mutation: 35-year follow-up of a large family - Anand Pathak; Alexander Pemov; Mary L. McMaster; Ramita Dewan; Sarangan Ravichandran; Evgenia Pak; Amalia Dutra; Hyo Jung Lee; Aurelie Vogt; Xijun Zhang; Meredith Yeager; Stacie Anderson; et al. (Human Genetics, 2015)

Molecular approaches for biodegradation of polycyclic aromatic hydrocarbon compounds: a review - Shalini Gupta; Bhawana Pathak; M. H. Fulekar (Reviews in Environmental Science and Bio/Technology, 2015)

Geostatistics-based groundwater-level monitoring network design and its application to the Upper Floridan aquifer, USA - Shirish Bhat; Louis H. Motz; Chandra Pathak; Laura Kuebler (Environmental Monitoring and Assessment, 2015)

Mitigation of greenhouse gas emission with system of rice intensification in the Indo-Gangetic Plains - Niveta Jain; Rachana Dubey; D. S. Dubey; Jagpal Singh; M. Khanna; H. Pathak; Arti Bhatia (Paddy and Water Environment, 2014)

Ammonia Emission from Rice–Wheat Cropping System in Subtropical Soil of India - S. K. Sharma; R. C. Harit; V. Kumar; T. K. Mandal; H. Pathak (Agricultural Research, 2014)

Impairment of Mitochondrial–Nuclear Cross Talk in Neutrophils of Patients with Type 2 Diabetes Mellitus - Saba Khan; Gorantla V. Raghuram; Neelam Pathak; Subodh K. Jain; Dolly H. Chandra; Pradyumna K. Mishra (Indian Journal of Clinical Biochemistry, 2014)

Trends and fluctuations of rainfall regime in the Brahmaputra and Barak basins of Assam, India - R. L. Deka; C. Mahanta; H. Pathak; K. K. Nath; S. Das (Theoretical and Applied Climatology, 2013)

Dry direct-seeding of rice for mitigating greenhouse gas emission: field experimentation and simulation - H. Pathak; S. Sankhyan; D. S. Dubey; A. Bhatia; N. Jain (Paddy and Water Environment, 2013)

Ammonia emission from subtropical crop land area in India - A. Datta; S. K. Sharma; R. C. Harit; V. Kumar; T. K. Mandal; H. Pathak (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Altered phosphorylation and distribution status of vimentin in rat seminiferous epithelium following 17β-estradiol treatment - Rahul Upadhyay; Ryan D’Souza; Shobha Sonawane; Reshma Gaonkar; Shilpa Pathak; Aditi Jhadav; N. H. Balasinor (Histochemistry and Cell Biology, 2011)

Mitigating greenhouse gas and nitrogen loss with improved fertilizer management in rice: quantification and economic assessment - H. Pathak (Nutrient Cycling in Agroecosystems, 2010)

Trade-off between productivity enhancement and global warming potential of rice and wheat in India - A. Bhatia; H. Pathak; P. K. Aggarwal; N. Jain (Nutrient Cycling in Agroecosystems, 2010)

Nitrogen, phosphorus, and potassium budgets in Indian agriculture - H. Pathak; S. Mohanty; N. Jain; A. Bhatia (Nutrient Cycling in Agroecosystems, 2010)

Eco-restoration of a high-sulphur coal mine overburden dumping site in northeast India: A case study - J. Dowarah; H. P. Deka Boruah; J. Gogoi; N. Pathak; N. Saikia; A. K. Handique (Journal of Earth System Science, 2009)

Global warming mitigation potential of biogas plants in India - H. Pathak; N. Jain; A. Bhatia; S. Mohanty; Navindu Gupta (Environmental Monitoring and Assessment, 2009)

Apoptotic signaling induced by benzamide riboside: an in vitro study - Sujata Pathak; Chandresh Sharma; H. N. Jayaram; Neeta Singh (Molecular and Cellular Biochemistry, 2009)

Quantitative evaluation of climatic variability and risks for wheat yield in India - H. Pathak; R. Wassmann (Climatic Change, 2009)

Site-specific nutrient management in rice in Eastern India using a modeling approach - D. K. Das; Debtanu Maiti; H. Pathak (Nutrient Cycling in Agroecosystems, 2009)

Stochastic Modeling of Progressive Failure in Heterogeneous Soil Slope - D. R. Pathak; H. N. Gharti; A. B. Singh; A. Hiratsuka (Geotechnical and Geological Engineering, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Simulation of Nitrogen Dynamics in Soil Using Infocrop Model - K. N. Ebrayi; H. Pathak; Naveen Kalra; Arti Bhatia; Niveta Jain (Environmental Monitoring and Assessment, 2007)

Long-term yield trend and sustainability of rainfed soybean–wheat system through farmyard manure application in a sandy loam soil of the Indian Himalayas - S. Kundu; Ranjan Bhattacharyya; Ved Prakash; H. S. Gupta; H. Pathak; J. K. Ladha (Biology and Fertility of Soils, 2006)

Molecular cloning, expression, and cytokinin (6-benzylaminopurine) antagonist activity of peanut (Arachis hypogaea) lectin SL-I - Monika Pathak; Bharat Singh; Amit Sharma; Praveen Agrawal; Santosh B. Pasha; Hasi R. Das; Rakha H. Das (Plant Molecular Biology, 2006)

Dynamics of Organic Carbon and Microbial Biomass in Alluvial Soil With Tillage and Amendments in Rice-wheat Systems - B. Banerjee; P. K. Aggarwal; H. Pathak; A. K. Singh; A. Chaudhary (Environmental Monitoring and Assessment, 2006)

Impact of Post-Methanation Distillery Effluent Irrigation on Groundwater Quality - N. Jain; A. Bhatia; R. Kaushik; Sanjeev Kumar; H. C. Joshi; H. Pathak (Environmental Monitoring and Assessment, 2005)

Use of Flyash and Biogas Slurry for Improving Wheat Yield and Physical Properties of Soil - R. N. Garg; H. Pathak; D. K. Das; R. K. Tomar (Environmental Monitoring and Assessment, 2005)

Soil Properties and Crop Productivity as Influenced by Flyash Incorporation in Soil - Naveen Kalra; M. C. Jain; H. C. Joshi; R. Chaudhary; Sushil Kumar; H. Pathak; S. K. Sharma; Vinod Kumar; Ravindra Kumar; R. C. Harit; S. A. Khan; M. Z. Hussain (Environmental Monitoring and Assessment, 2003)

Major Indian expeditions ofSaccharum complex - A. D. Pathak; H. M. Srivastava; N. Kulshreshtha (Sugar Tech, 2003)

Modelling the quantitative evaluation of soil nutrient supply, nutrient use efficiency, and fertilizer requirements of wheat in India - H. Pathak; P.K. Aggarwal; R. Roetter; N. Kalra; S.K. Bandyopadhaya; S. Prasad; H. Van Keulen (Nutrient Cycling in Agroecosystems, 2003)

Effects of dicyandiamide, farmyard manure and irrigation on crop yields and ammonia volatilization from an alluvial soil under a rice ( Oryza sativa L.)-wheat ( Triticum aestivum L.) cropping system - Banerjee B.; Pathak H.; Aggarwal P. (Biology and Fertility of Soils, 2002)

The role of potassium in sustaining yields in a long-term rice-wheat experiment in the Indo-Gangetic Plains of Nepal - Regmi A.; Ladha J.; Pasuquin E.; Pathak H.; Hobbs P.; Shrestha L.; Gharti D.; Duveiller E. (Biology and Fertility of Soils, 2002)

Emission of Nitrous Oxide from Rice-Wheat Systems of Indo-Gangetic Plains of India - H. Pathak; Arti Bhatia; Shiv Prasad; Shalini Singh; S. Kumar; M. C. Jain; U. Kumar (Environmental Monitoring and Assessment, 2002)

Nitrous Oxide Emission from Soil with Different Fertilizers, Water Levels and Nitrification Inhibitors - H. Pathak; D. B. Nedwell (Water, Air, & Soil Pollution, 2001)

Long-term changes in yield and soil fertility in a twenty-year rice-wheat experiment in Nepal - Gami S.; Ladha J.; Pathak H.; Shah M.; Pasuquin E.; Pandey S.; Hobbs P.; Joshy D.; Mishra R. (Biology and Fertility of Soils, 2001)

Mitigation of N 2 O emission from an alluvial soil by application of karanjin - Majumdar D.; Dutta A.; Kumar S.; Pathak H.; Jain M. (Biology and Fertility of Soils, 2001)

Nitrous oxide emission from different fertilizers and its mitigation by nitrification inhibitors in irrigated rice - U. Kumar; M. C. Jain; H. Pathak; S. Kumar; D. Majumdar (Biology and Fertility of Soils, 2000)

Soil Amendment with Distillery Effluent for Wheat and Rice Cultivation - H. Pathak; H. C. Joshi; A. Chaudhary; R. Chaudhary; N. Kalra; M. K. Dwiwedi (Water, Air, & Soil Pollution, 1999)

Insect drift over the northern Arabian sea in early summer - S. C. Pathak; Vandana Kulshrestha; Arun Kumar Choubey; A. H. Parulekar (Journal of Biosciences, 1999)

Relationship between sugar maple decline and corresponding chemical changes in the stem tissue - H. K. Mohamed; S. Pathak; D. N. Roy; T. C. Hutchinson; D. L. McLaughlin; J. C. Kinch (Water, Air, & Soil Pollution, 1997)

RELATIONSHIP BETWEEN SUGAR MAPLE DECLINE AND CORRESPONDING CHEMICAL CHANGES IN THE STEM TISSUE - H. K. MOHAMED; S. PATHAK; D. N. ROY; T. C. HUTCHINSON; D. L. MCLAUGHLIN; J. C. KINCH (Water, Air, & Soil Pollution, 1997)

The Imperata grasslands of tropical Asia: area, distribution, and typology - D. P. Garrity; M. Soekardi; M. van Noordwijk; R. de la Cruz; P. S. Pathak; H. P. M. Gunasena; N. van So; G. Huijun; N. M. Majid (Agroforestry Systems, 1996)